Rapid analysis of polybrominated diphenyl ethers by ion attachment mass spectrometry - Sato, Yuka; Oki, Mitsuhiro; Kondo, Asato; Takenaka, Miyuki; Satake, Hideki (Analytical methods, 2010)
Novel rapid analytical method was developed for evaluating polymers for the presence of polybrominated diphenyl ethers (PBDEs), which have been prohibited by the RoHS directive, using ion attachment mass spectrometry (IAMS). IAMS requires no chemical pretreatment or separation process for the individual organic compounds before analysis because of its “soft” ionization feature. When measurement was performed for a standard solution of decabromodiphenly ether (decaBDE), no fragment ions were detected. The optimum analysis conditions for polymers were determined using reference materials. When polymers containing decaBDE were analyzed by IAMS under the optimum conditions, a decaBDE concentration of approximately 300 ppm (in the case of 1-mg solid sample for analysis) could be detected with no fragmentation. Even if other brominated compounds, such as ethylene (bis-tetrabromophthal)imide (EBTBPI) and bis(pentabromophenyl)ethane (BPBPE) were present in the sample together with decaBDE, each compound could be identified successfully. In addition, with respect to the validation of IAMS, it was confirmed the limit of detection (LOD) and the limit of quantification (LOQ) for decaBDE were 13.5 and 45.0 ppm (in the case of 1-mg solid sample for analysis), respectively, and that the calibration curve showed good linearity (R² = 0.9962) within the range of 0.04 to 2.00 μg. The recovery of the decaBDE from the certified reference materials was 81.4% for the 317-ppm sample and 85.4% for 886-ppm sample.